Electrical and optical characterization of CO2/He glow discharge. (March 2015) - Reyes, P G; Torres, C; Torres, J; Gómez, A; Martínez, H; Vergara, J
Abstract: Glow discharge studies are produced in a atmosphere of CO2 /He mixture at a pressure of 1.5 Torr . The experiment was conducted to observe the optical emission spectroscopy of the plasma, and determined the electron temperature and ion density by the use of a double Langmuir probe. The electron temperature of the mixture was found in the range of 4.54 to 5.37 eV, and the ion density values between 2.15 and 12.00 × 10 9 particles/cm 3 . The principal species observed were: CO2 + CO +, CO, C2, O2 + O *, and He * .